Aphasia: Definition, clinical contexts, neurobiological profiles and clinical treatments - Giulio Perrotta (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2020)
Starting from the general concept of Aphasia, the present work focuses on the clinical, neurobiological, and functional aspects of the morbid condition, suggesting a multidimensional treatment between physiotherapy, psychotherapy, and rehabilitation exercises for lost skills.